Comparative study of safety and efficacy of pregabalin and gabapentin in management of neuropathic pain associated with chronic lumbar radiculopathy - Shaikh, Huzaif; Syed, Maaz H.; Khan, Imran N.; Mubeen, Faheem (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chronic lumbar radiculopathy a clinical condition in which there is back and leg pain associated with sensory, reflex, or motor deficits in the area of nerve root distribution lasting for more than 12 weeks. The prevalence of lumbar radiculopathy has been reported to be 5.3% in men and 3.7% in women. Pregabalin and gabapentin, which fit in to a new category of drugs called as alpha-2-delta (α2δ) modulators, have been discovered to be effective in the treatment of neuropathic pain related with multiple conditions. So this study was done to compare safety and efficacy of pregabalin and gabapentin in management of pain associated with chronic lumbar radiculopathy. Methods: This was a randomized two arm comparative prospective study. Total 160 patients were enrolled and randomized equally into 2 groups. Group A patients were given capsule pregabalin 75 mg two times a day orally, Group B patients were given tablet gabapentin 300 mg two times a day. Pain intensity was assessed at the start of study i.e. at baseline (0 week), at 6 weeks and at 12 weeks of starting the treatment using numeric pain rating scale. Results: There was significant reduction in pain at the end of 12 weeks in both the groups (p<0.0001), but there was no significant difference between these two groups. The incidence of adverse effects was also more in group A. Conclusions: Both the drugs are having comparable efficacy but gabapentin is more tolerable in such cases.